A voice operated relay / Nor Hasnah Hassan - Hassan, Nor Hasnah (1985)
Voice operated relay is actually a device allows virtually hand-free operation of the radio. It sampled the sound from a microphone and switched a relay when the level of the microphone exceed the preset level. The relay is held on as long as the sound level stays above the threshold and when the micrphone drop below the critical level the relay are off.